High expectations, varying outcomes: Decentralization and participation in Brazil, Japan, Russia and Sweden - Andrews, Christina W.; de Vries, Michiel S. (Sage Publications Ltd, 2007)
In the past 20 years, decentralization has been proposed as a strategy for enhancing public participation. Aid-providing organizations, such as the World Bank, stimulated decentralization processes in several countries in the hope that this would promote civic empowerment, diminish corruption, enhance efficiency, and improve public service delivery. This assumption forms the basis for a comparative analysis into the relation between decentralization and participation at the local level in Brazil, Japan, Russia and Sweden. A multi-level regression analysis using the data of the Democracy and Local Governance Project was undertaken in order to test the 'one size fits all' and the 'diversity in development' hypotheses. The results show that the second hypothesis was corroborated. Perceived autonomy had a different impact on openness to participation depending on the country considered; in one country (Japan), perceived autonomy diminished public officials' willingness to be open to public participation.